2023
DOI: 10.1002/cplu.202200390
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous‐Flow Microreactor for Knoevenagel Condensation of Ethyl Cyanoacetate with Benzaldehyde: The Effect of Grafted Amino Groups on Catalytic Activity

Abstract: Ethyl α‐cyanocinnamate was synthesized in the Knoevenagel condensation of benzaldehyde and ethyl cyanoacetate in flow monolithic microreactor of 0.63 cm3 volume. The catalytically active core was made of silica monolith modified with various amine group precursors. Structural properties of the support, surface density of NHx groups, and catalytic activity were investigated. It was found that the poly‐ or di‐amine groups attached to the silica surface appeared to be more effective than the aminopropyl groups. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The conversion of BDMA was signi cantly higher (98%), which con rmed negative effect of methyl group on a course of the hydrolysis reaction. However, yield of EEC was smaller (68%) in agreement with our previous studies [29], which showed that a hydrophobic environment increases the e ciency of the condensation reaction. The negative impact of neighbouring groups is hardly visible in the Knoevenagel reaction (entry 2 vs. 9), which con rmed that there is no interaction between acid sites located on the silica surface and the amine groups attached via propyl linker.…”
Section: Catalytic Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The conversion of BDMA was signi cantly higher (98%), which con rmed negative effect of methyl group on a course of the hydrolysis reaction. However, yield of EEC was smaller (68%) in agreement with our previous studies [29], which showed that a hydrophobic environment increases the e ciency of the condensation reaction. The negative impact of neighbouring groups is hardly visible in the Knoevenagel reaction (entry 2 vs. 9), which con rmed that there is no interaction between acid sites located on the silica surface and the amine groups attached via propyl linker.…”
Section: Catalytic Resultssupporting
confidence: 92%
“…Decomposition of functional groups was observed in the range of 180-700°C. In this process, not only organic amino groups were released, but also ethyl groups, which were attached to the silica surface during grafting as a result of the esteri cation reaction of ethanol with surface hydroxyls, as was discussed earlier [29]. The DTG curve clearly showed the well-developed peaks with maxima at 280°C and 350°C, which indicated that thermal decomposition of aminoethylaminopropyl group occurred in two steps.…”
Section: Characterisation Of Monolithic Coresmentioning
confidence: 61%
See 1 more Smart Citation
“…Knoevenagel condensed continuous flow microreactor has been reported for a long time. [16] Formic acid was used as the chosen catalyst, with a total flow rate of 0.2 ml/min and a back pressure of 75PSI. The equivalents of p-benzaldehyde were sequenced (refer to Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted the Knoevenagel condensation reaction. Knoevenagel condensed continuous flow microreactor has been reported for a long time [16] . Formic acid was used as the chosen catalyst, with a total flow rate of 0.2 ml/min and a back pressure of 75PSI.…”
Section: Resultsmentioning
confidence: 99%